International Market Development Strategies for Enhancing Global Expansion in the Export Industry - Muhlisah Lubis; Balakrishnan Muniapan (Involvement International Journal of Business, 2024)
This research paper explores a range of international market development strategies that companies can adopt to enhance global expansion in the export industry. The study emphasizes the significance of conducting comprehensive market research, which enables businesses to identify target markets with high demand and subsequently improve market penetration and increase export sales. Furthermore, the findings highlight the importance of market segmentation in tailoring offerings to meet specific market needs, resulting in higher customer satisfaction and a larger market share. The research also reveals that conducting competitive analysis is crucial for companies to differentiate their offerings, develop competitive advantages, and improve their market positioning, ultimately leading to increased market share. The study underscores the importance of selecting the appropriate entry mode, such as direct exporting, licensing, or joint ventures, as it significantly impacts the success of global expansion efforts. Additionally, the research emphasizes the significance of developing efficient distribution channels to ensure timely and cost-effective delivery of products, thereby enhancing customer satisfaction and facilitating market penetration. The findings also stress the importance of adapting branding and marketing strategies to align with local cultural preferences and linguistic nuances, which helps establish a strong brand presence, foster customer loyalty, and gain market acceptance. Moreover, the research highlights the role of government support, trade agreements, and financial incentives in facilitating global expansion. Leveraging these resources provides companies with valuable market insights, resources, and financial assistance, thereby bolstering their international expansion endeavors.